Hanzyuk A.L., Оleksandrenko V.P., Nesdorovin V.P. The influence of fretting-processes on the composition of mixtures of alcohol. - Ганзюк, А.Л.; Олександренко, В.П.; Нездоровін, В.П. (Problems of Tribology, 2017)
Conducted chromatographic study of the effect of fretting processes in alcohol environments on ScrollPoint the composition of alcohol. and structural changes of the metal surfaces of samples of steel 30ХГСA. Tribo-chemical reactions take place in the tribo-system, i.e. both in metal and in ethanol medium. The emission of electrons from the metal initiates the formation of free radicals in the alcohol solution, which then form more complex organic compounds. The ejection of elec-trons from metal surface to the environment leads to an increase in their concentration in the medium and initiates the flow of tribo-chemical reactions, which by their nature differ significantly from chemical. The erosion of the metal takes place by rupture of the metal ties under the action tribology fluctuations when there are variations of atoms with large amplitude.Found that low-amplitude cyclic fluctuations initiate the flow of complex tribo-chemical reactions which from the more simple structure of organic compounds formed more complex and changing ScrollPoint the composition of alcohol, namely increasing the number of ester – tamilanadu that has the most complex structural formula.Key words: framing-the process of tribo - chemical reaction, scrollpoint the composition of alcohol.